Issue ownership attack: how a political party can counteract a rival's issue ownership. Issue 4 (6th June 2020) - Seeberg, Henrik Bech
Abstract: A central part of representative democracy is that voters evaluate political parties based on how competently they handle issues, so-called 'issue ownership'. Since issue ownership is a central ingredient in the vote choice, rival parties often try to influence how voters evaluate a competing party. This is an issue ownership attack. However, despite intense scholarly interest in issue ownership, the understanding of how parties shape issue ownership is very limited. Therefore a new theoretical model is tested here to understand issue ownership attack. Using several survey experiments, the analysis shows that a mainstream party can counteract another mainstream party's issue ownership by reframing the issue and by blaming the party for its performance, but not by changing its own position on the issue. Hence, the study not only advances the understanding of issue ownership stability and change but also brings important insights on how parties influence voters.